International Borrowing: A Reply To Rolf Mirus's Note - Jucker, James V. (Journal of International Business Studies, 1978)
Rolf Mirus starts his note on international borrowing by describing the “approach” which Clovis de Faro and I took in our JIBS article as that of “… picking the [borrowing] source with least expected cost without consideration of the risk involved.”1 This characterization of our work is somewhat unfortunate, since we assumed, for purposes of clarity and simplicity, that the borrowing problems considered were situated in a deterministic (i.e., riskless) world. Specifically, we assumed that “…the inflation rates and devaluation rates expected during a loan period are always realized.”2 Perhaps we should have repeated this assumption at the end of the paper and emphasized the limitations that this places on our results. Had we done this we might well have included something along the lines of the following: “That a firm in a risky world may refrain from raising all of its required funds in a lower cost foreign market is not contrary to the simple decision rule developed here, for our rule was developed for a riskless world.”